2016
DOI: 10.1038/srep33885
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of Arabidopsis thaliana under single-wavelength red and blue laser light

Abstract: Indoor horticulture offers a sensible solution for sustainable food production and is becoming increasingly widespread. However, it incurs high energy and cost due to the use of artificial lighting such as high-pressure sodium lamps, fluorescent light or increasingly, the light-emitting diodes (LEDs). The energy efficiency and light quality of currently available horticultural lighting is suboptimal, and therefore less than ideal for sustainable and cost-effective large-scale plant production. Here, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 65 publications
(109 reference statements)
0
39
0
Order By: Relevance
“…Recently, Ooi et al (2016) has also demonstrated the use of high-powered single-wavelength red and blue laser lights for indoor horticulture using Arabidopsis . However, the potential application of laser light for sustainable food production needs further research with more crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ooi et al (2016) has also demonstrated the use of high-powered single-wavelength red and blue laser lights for indoor horticulture using Arabidopsis . However, the potential application of laser light for sustainable food production needs further research with more crops.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that shoot DW increased with increasing red/blue light ratio, which was mainly due to increased leaf number and leaf area under the higher red/blue light ratio. It was also reported that the optimal red/blue light ratios for FW and DW accumulation were 7/3 in strawberry plantlet (Nhut et al, 2003) and 1/3 in rapeseed plantlets in vitro (Li et al, 2013), respectively, but 9 in cucumber seedlings (Hernández and Kubota, 2016), spinach (Yorio et al, 2001), lettuce (Bula et al, 1991; Yorio et al, 2001; Stutte et al, 2009), and Arabidopsis (Ooi et al, 2016). Based on the above discussion, blue light promote growth by stimulating morphological response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One feature of existing speed breeding systems is the use of LEDs to improve light quality and reduce operational costs 12,15 . Instead, laser light could be used to reduce costs further because it has a higher electrical conversion efficiency, with 40-60% of energy being converted into light, depending on the light color 72 (Fig. 5e).…”
Section: Review Articlementioning
confidence: 99%
“…As well as boosting growth and increasing returns on energy input, laser light can be generated outside a growth cabinet or greenhouse,   beamed inside and then scattered over plants, eradicating much of the cooling costs that make crop research in controlled environments expensive. Arabidopsis thaliana plants grown under these conditions exhibit reduced expression of certain proteins that are associated with light and radiation stress in comparison to those grown under cool-white fluorescent light 72 ; higher photon irradiance intensities could therefore be applied using this approach with less damage to the plant (Fig. 5g).…”
Section: Review Articlementioning
confidence: 99%